2023
DOI: 10.3389/fmicb.2023.1232086
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the efficacy of 1-amino-cyclopropane-1-carboxylic acid (ACCA) as a natural compound in strengthening maize resistance against biotic and abiotic stressors: an empirical computational study

Sandip Debnath,
Abdallah M. Elgorban,
Ali H. Bahkali
et al.

Abstract: ObjectiveThis study aims to understand plant-bacteria interactions that enhance plant resistance to environmental stressors, with a focus on maize (Zea mays L.) and its vulnerability to various pathogenic organisms. We examine the potential of 1-amino-cyclopropane-1-carboxylic acid (ACCA) as a compound to boost maize’s resilience against stressors and pathogens.BackgroundWith the growing global population and increased food demand, the study of endophytes, comprising bacteria and fungi, becomes crucial. They r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The OPLS 2005-derived force field was employed during the simulation ( Xu et al., 2023 ). The physiological circumstances present during the experiment were simulated by introducing a concentration of 0.15 M by the utilization of NaCl ( Debnath et al., 2023a ). The simulation was conducted at a temperature of 300 K and a pressure equivalent to atmospheric pressure.…”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The OPLS 2005-derived force field was employed during the simulation ( Xu et al., 2023 ). The physiological circumstances present during the experiment were simulated by introducing a concentration of 0.15 M by the utilization of NaCl ( Debnath et al., 2023a ). The simulation was conducted at a temperature of 300 K and a pressure equivalent to atmospheric pressure.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Importantly, in our recent study on maize ( Zea mays L.), we explored the role of 1-amino-cyclopropane-1-carboxylic acid (ACCA) in enhancing plant resistance. We found that ACCA, with a binding energy of −9.98 kcal/mol, effectively strengthens maize against pathogens and drought stress ( Debnath et al., 2023a ). This finding is pivotal for our current research on cauliflower, as it suggests ACCA’s broader applicability in different plant species.…”
Section: Introductionmentioning
confidence: 99%